Comparison of selected digital modulation schemes (OOK, PPM and DPIM) for wireless optical communications - Mahdiraji, G.A.; Zahedi, E. (IEEE, 2006)
In this article, three digital modulation schemes popular in optical wireless communication systems (OOK, PPM and DPIM) are compared based on bandwidth requirement, power efficiency, transmits-ion capacity and biterror probability. In OOK, the bandwidth requirement is roughly equivalent to the data rate (Rb). PPM achieves higher average power efficiency than OOK at the expense of an increased bandwidth ( 4) compared to OOK. Besides, the use of PPM imposes more system complexity compared to OOK since both slot- and symbol-level synchronizati-ons, critical to system performance, are required at the receiver. Unlike PPM, DPIM does not require symbol synchronization since each symbol is initiated with a pulse. Furthermore, DPIM displays a higher transmiss-ion capacity by eliminating all the unused time slots from within each symbol. In terms of BER, 4-DPIM displays a performance in between that of OOK and PPM. It is concluded that DPIM is the most efficient scheme in terms of transmission capacity and band-width requirements. When it comes to power and error performance, PPM is the best among the three schemes.